On chip preconcentration and fluorescence labeling of model proteins using monolithic columns: device fabrication, optimization, and automation - Yang, Rui (Anal Bioanal Chem, 2014)
Microfluidic systems are developed with monolithic columns for preconcentration and on-chip labeling of model proteins. Monoliths are prepared in microchannels via photopolymerization, and the properties of monoliths are optimized by varying the composition and concentration of monomers to improve flow and extraction. On-chip labeling of proteins is achieved by driving solutions through the monolith using voltage and incubating fluorescent dye with protein retained in the monolith. Subsequently, the labeled proteins are eluted by applying voltages to reservoirs on the microdevice and then detected by laser-induced fluorescence. Monoliths prepared from octyl methacrylate show the best combination of protein retention while still allowing unattached fluorescent label to be eluted in a separate fraction with 50% acetonitrile. Finally, automated on-chip extraction and fluorescence labeling of a model protein is successfully demonstrated. This work provides facile sample pretreatment, and therefore offers promising potential for future integrated bioanalysis microchips.